Desenvolvimento e aplicação de método para determinação de trifluralina em material particulado atmosférico - Santos Junior, Wilson Zimmermam (2016)
Air pollution is any form of matter or energy that can make air harmful to human health, fauna, flora and materials. Among the many forms of pollution is the atmospheric particulate material, which in addition to causing numerous respiratory diseases can carry a wide range of toxic substances, among them the agrochemicals used in agriculture. This work aims to develop and apply an analytical method for the determination of Trifluralin in atmospheric particulate material. Firstly, the cleaning of the filters used in the sampling and the possible interferences from the solvent. A sampling plan was establish to be carried out in the city of Arapongas, Paraná. Two solutions of Trifluralin at a concentration of 1.21 mg L-1 in methanol and ethyl acetate were prepared. Then the chromatographic conditions for the analysis of the herbicide were evaluate by high performance liquid chromatography coupled to a diode array detector (HPLC-DAD) and for gas chromatography coupled to triple quadrupole mass spectrometry (GC-MS/MS). For these two devices the limits of detection and quantification, the extension of the linear range and the selectivity were evaluated. Due to the low concentration of the analyte in the matrix two preconcentration conditions were evaluated in rotavaporator. Then the extraction was tested via: the ultrasonic bath, mechanical agitation and extraction via Soxhlet. All extractions were performed using a 1: 2: 1 mixture of acetone: dichloromethane: hexane. After defining the extraction method, the clean up step was evaluated using 1 g of florisil as an adsorbent and an eluting solution composed of 1: 1 acetone: hexane. The chromatographic conditions, extraction method, clean up and preconcentration were performed fortification and recovery in a sample of the herbicide-free particulate material to evaluate the accuracy and precision of the method and also to evaluate the presence of a possible effect of matrix. Finally, quantification of Trifluralin present in the collected particulate material of Arapongas-PR was carried out. This test was carried out in three levels of fortification. Calcination was effective and removed potential interferents that could coelute with the analyte. Both chromatographic techniques had low limits of detection and quantification, with the limit of detection of HPLC-DAD was 37.2 pg m-3 and the limit of quantification was 124 pg m-3, whereas GC-MS / MS showed a detection limit of 0.39 pg m-3 and a limit of quantification of 1.29 pg m ,both techniques also showed selectivity for the determination of Trifliralin in atmospheric particulate material. The extraction performed by Soxhlet equipment and by ultrasonic bath showed good recoveries, the same was not observed for the mechanical agitation. The clean up step presented the ability to remove possible interferents and also proved to be an essential step for the analytical method, removal of these substances prevented the clogging of the 0.2 μm filtration membranes. Fortification and recovery tests demonstrated that the method is accurate and accurate for the determination of Trifluralin in atmospheric particulate material and also demonstrated an intense associated matrix effect which was corrected using the matrix superimposition technique. The atmospheric particulate material collected in the Arapongas PR region presented low concentrations of Trifluralin and in some cases the herbicide was not detected. The proposed method proved to be accurate, accurate and capable of detecting and quantifying Trifluralin present in atmospheric particulate material even at low levels of contamination.